Experimental evaluation of strength characteristics of different Egyptian soils using enzymatic stabilizers. Issue 1 (1st January 2018) - AbouKhadra, Abdullah; Zidan, Ahmed F.; Gaber, Yasser
Abstract: Soils with poor bearing capacities represent a challenge to construction engineers, therefore continuous investigation of different additives and stabilizers is sought in order to improve such weak soils and reduce the cost of replacement. In this paper, an experimental program is adopted to investigate the effect of environmentally friendly material based on enzymes on the soil performance. The effect of different dosages of two commercial enzymatic preparations on the soil strength, maximum dry density and permeability of five different soils was examined. Besides, California Bearing Ratio (CBR) and unconfined compressive strength (UCS) were conducted to investigate the enhancement in soil strength. X-ray fluorescence (XRF) analysis showed a slight increase in the silica ion content in the treated soils. It is inferred from the results that using the enzymatic preparations significantly increased the strength of fine soil, the rate of improvement was found to be proportional to the clay content in the soil.